Nigeria and OPEC : to be or not to be - Nwankwo, G. O. (Ibadan : African Universities Press, 1983)
The book is divided into three parts: The Place of the Petroleum Industry in Nigeria, Oil Glut: Effects on Government Financing, and Nigeria and OPEC: To Be or Not To Be.
Includes bibliographies.
rpm 22/01/2019
Loans
Keywords: Petroleum industry and trade